2004
DOI: 10.1038/sj.gene.6364140
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the mannose-binding lectin gene in primates

Abstract: The mannose-binding lectin MBL2 plays an important role in the innate immune system. It binds carbohydrates surface, acts as an opsonin and activates the complement system. With the aim of studying the evolution of the MBL2 gene in primates, we sequenced its coding region in 12 non-human primate species and compared them with the human sequence. We demonstrated that nucleotide and amino-acidic sequences of the MBL2 among primates are highly homologous, underlining the importance of this molecule in the defense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The exon structure of the MBL2 gene is extremely well preserved between humans and other higher primates [49]. In particular, the homology in the collagen-like domain among primates is very high, and the MBL2 gene from primates seems not to carry analogue variants similar to those that are so prevalent in humans.…”
Section: Mbl2 Polymorphismsmentioning
confidence: 97%
“…The exon structure of the MBL2 gene is extremely well preserved between humans and other higher primates [49]. In particular, the homology in the collagen-like domain among primates is very high, and the MBL2 gene from primates seems not to carry analogue variants similar to those that are so prevalent in humans.…”
Section: Mbl2 Polymorphismsmentioning
confidence: 97%
“…It has been shown that the exon structure in the MBL2 gene is extremely well preserved between human and higher primates. 49 In particular, the collagen-like domain is identical in humans, chimpanzees and gorillas at the amino-acid level and the difference in the whole protein is less than 1%. These few amino-acid differences do not result in changes of the structure or function of MBL.…”
Section: Historical Backgroundmentioning
confidence: 98%
“…These results showed that intermediate forms were found in higher primates suggesting that the ancestral human MBL2 haplotype may have arisen in the evolutionary gap between LYQA and LYPA haplotypes. The exon structure of MBL2 is extremely well preserved between humans and higher primates . In particular the collagen‐like domain is almost identical, while some differences are observed in the CRD region.…”
Section: Mblmentioning
confidence: 99%